The relations between dietary antioxidant vitamins intake and oxidative stress in follicular fluid and ART outcomes - Ashraf Kazemi; Fatemeh Ramezanzadeh; Mohammad Hosein Nasr-Esfahani (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Oxidative stress (OS) in the follicular environment may affect on oocyte competence and antioxidant vitamins may modify its effects. Objective: This study was conducted to examine the effect of dietary intake of vitamin A, C and E on OS in follicular environment and assisted reproduction technology (ART) outcomes. Materials and Methods: In this obsevationalprospective study, the intake levels of vitamin A, C, and E were matured by validated food frequency questionnaire and Malondialdehyde and the total antioxidant capacity (TAC) levels of follicular fluid (FF) in 219 women undergoing ART were assessed. The number of retrieved oocytes, percentages of metaphase II MII) stage oocytes, fertilization rate, and embryo quality were also determined. Results: No significant association was found between vitamins intake levels and OS biomarkers, but the mean of TAC level in FF among women who received vitamin C greater than 75 mg/d was higher than women with lower intakes (p<0.05). The ART parameters were not related to the vitamin E intake level, but the normal cleaved embryo rate was positively related to vitamin A (p<0.05) and vitamin C (p=0.02) intake levels. Also, the percentage of MII oocytes (p=0.02) and the fertilization rate (p<0.05) were related to the vitamin C intake level. The relation between the TAC level in FF and ART outcomes were not significant. Conclusion: Current results indicated that high dietary intake of vitamin C would be followed by increasing the TAC level in FF and improving the oocyte competence, but this effect of vitamin C is not dependent of increasing of antioxidant defense in follicular environment.